PEMBELAJARAN MEMBACA DAN MENULIS DENGAN MENGGUNAKAN METODE SUKU KATA BAGI ANAK-ANAK DUSUN EMBUR LAUK DESA PRINGGABAYA - Sabahiyah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2021)
The purpose of holding this community service activity that the children in Embur Leuk Pringgabaya Village can read and writen. This activity was carried out because there where still children in Embur Leuk, who cannot read and writen even though they were at the elementary school level. This activity was attended by 15 elementary school children from different grade levels. The method of implementing this service activity is a survey of activity needs, planning activites, implementation activites, and evaluations. While the method used in learning activites, using the syllable method and the media used is syllable card media. The result of this activitity show that the children in Embur Leuk, Pringgabaya Village were very enthusiastic when the learning process takes place and they are also satisfied because they can read an write.